2017
DOI: 10.25299/jshmic.2017.vol4(1).512
|View full text |Cite
|
Sign up to set email alerts
|

Listening Comprehension Hindrances of EFL (English Foreign Language) Learners on 2016/2017 in English Study Program of Universitas Islam Riau

Abstract: As one of essential skills to master a language, listening subject is provided as one of compulsory subjects to the learners in English study program at university level in order to help them in improving their English skill in term of having good ability in comprehending spoken information delivered by native or non-native speakers of English in various contexts of communication. Despite of having long term English learning experiences and easy access of learning sources, the learners seem still having hindra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Listening skill has important roles to all other skills because it can significantly influence for language development, (Bang and Hiver, 2016 Hadijah and Shalawati (2017) in their study about listening comprehension hindrances of EFL learners also found that lack of listening practices at schools as main factor affecting the learners' listening comprehension. Then, it links to the learners' unfamiliarity of speakers' speech rate, pronunciation, and unknown vocabulary.…”
Section: Listening Comprehensionmentioning
confidence: 98%
“…Listening skill has important roles to all other skills because it can significantly influence for language development, (Bang and Hiver, 2016 Hadijah and Shalawati (2017) in their study about listening comprehension hindrances of EFL learners also found that lack of listening practices at schools as main factor affecting the learners' listening comprehension. Then, it links to the learners' unfamiliarity of speakers' speech rate, pronunciation, and unknown vocabulary.…”
Section: Listening Comprehensionmentioning
confidence: 98%
“…Gilakjan and Sabowri (2016) indicated that listening is one of the most important skills in language instruction because when learners listen to English language, they face various listening difficulties since universities and schools focus more on writing, reading and vocabulary. In addition, studies by Hadijah & Shalawati (2016, 2017 showed that the learners' success on listening activities is affected by limited vocabulary mastery, unfamiliarity with the English words sound, speed rate of speakers in the audio or video, and also lack of strategy in learning. Therefore, in recent years there has been an increased focus on foreign language listening ability because of its perceived importance in language learning and acquisition.…”
Section: Introductionmentioning
confidence: 99%